Neither Corporate, Nor Family: The Indian “Patronal” Farm - Aubron, Claire; Bainville, Sébastien; Philippon, Olivier; Dorin, Bruno (Frontiers in Sustainable Food Systems, 2022)
After the disappearance of socialist State farms and cooperatives, the diversity of farms in the world seemed to have been reduced to a simple dichotomy: family farms on the one hand and corporate farming on the other. The former category, the dominant model on the planet, includes undertakings where labour is provided by the family, while corporate farming that was long limited to South America, is exclusively based on hired labour. This reading grid, however, turns out to be particularly problematic when looking at the Indian case. Despite their small size, a considerable number of Indian farms make use of a combination of family and hired labour. Based on an analysis of national statistics and fieldwork in thirteen small regions, this article characterises agricultural work and how family and hired labour function together on Indian farms. It shows that alongside family farms where wage labour (either hiring or being hired) serves to ensure full employment for family labour, there is another type of farm, which we define as “patronal farm”, where hiring agricultural labourers increases the income earned by family labour. In our surveys, this is systematically the case for irrigated agriculture, where wages paid to labourers are lower than the agricultural labour productivity per workday. After describing the characteristics of this original model, the article discusses its coherence with India’s political economy and questions its sustainability.